Capacity configuration optimization of multi-energy system integrating wind turbine/photovoltaic/hydrogen/battery. (1st August 2022) - Zhang, Yi; Sun, Hexu; Tan, Jianxin; Li, Zheng; Hou, Weimin; Guo, Yingjun
Abstract: Wind and solar energy are paid more attention as clean and renewable resources. However, due to the intermittence and fluctuation of renewable energy, the problem of abandoning wind and photovoltaic power is serious in China. Hydrogen production by water electrolysis is the effective way to solve the problem of renewable energy absorption. However, the multi-energy system has several optimization objectives for the capacity configuration, which are generally conflicting. The "impossible triangle" problem in the system is difficult to solve. Furthermore, the system capacity configuration is greatly affected by factors such as operating mode and energy storage form, etc. Therefore, the three different application scenarios are proposed both in the off-grid and grid-connected system, in which the energy storage system consists of only battery, only hydrogen, both hydrogen and battery, respectively. The system operation strategy is based on that the main purpose of hydrogen energy is storage, transportation and utilization alone. The multi-objective capacity configuration optimization based on the improved NSGA-Ⅱalgorithm is proposed, which is verified to be superior to NSGA-Ⅱand MOPSO. The capacity configurations of off-grid and grid-connected multi-energy systems are compared and analyzed. The economy of grid-connected system is better than that of off-grid system. The sensitivity analysis of important parameters is carried out such as wind/solar resources, load level and equipment price. The average wind speed has the significant impact on the net present value of the system. The capacity configuration and operation strategy proposed in this paper are effectively feasible to increase the renewable energy accommodation and meet comprehensive performance requirements of multi-energy complementary system. Highlights: Improved NSGAⅡalgorithm for capacity configuration can solve "impossible triangle" problem. Different energy storage forms are analyzed in off-grid and grid-connected systems. Hydrogen comprehensive utilization is superior to its electrical power regulation. Relationship between net present value and sensitive factors is analyzed.